High‐Efficiency Perovskite Solar Cells Based on New TPE Compounds as Hole Transport Materials: The Role of 2, 7‐ and 3, 6‐Substituted Carbazole Derivatives1. Issue 18 (7th March 2017) - Zhu, Linna; Shan, Yahan; Wang, Rui; Liu, Debei; Zhong, Cheng; Song, Qunliang; Wu, Fei
Abstract: In this work, four tetraphenylethylene (TPE)‐centered hole transport materials (HTMs), with 2, 7‐ or 3, 6‐substituted carbazole derivatives as periphery groups are deliberately synthesized and characterized. Their photophysical properties, energy levels, and photovoltaic performances are systematically investigated, and their performances as HTMs are discussed with respect to the different substituent positions on the carbazole moiety. It is interesting to find that the TPE‐based HTMs with 2, 7‐carbazole substituents rival the 3, 6‐carbazole substituents in hole mobility and hole extraction ability. A high power conversion efficiency of up to 16.74 % is achieved for the devices based on the 2, 7‐carbazole periphery arms, which is even higher than the one of the "star" HTM Spiro‐OMeTAD (2, 2‐7, 7‐tetrakis( N, N ′‐diparamethoxy‐phenylamine 9, 9′‐spirobifluorene) under the same conditions. As far as we know, this is the highest efficiency achieved in tetraphenylethylene derivatives. Abstract : Outperforming the star : Four tetraphenylethylene‐centered hole transport materials (HTMs) with 2, 7‐ or 3, 6‐substituted carbazole derivatives are synthesized and applied in perovskite solar cells. The 2, 7‐carbazole‐based HTMs show higher performance than the 3, 6‐carbazole‐based HTMs (see figure; FTO= fluorine tin oxide, FF=fill factor).